HEALTH TECHNOLOGY ASSESSMENT EVIDENCE ON E-HEALTH/M-HEALTH TECHNOLOGIES: EVALUATING THE TRANSPARENCY AND THOROUGHNESS. (19th February 2018) - Vukovic, Vladimir; Favaretti, Carlo; Ricciardi, Walter; de Waure, Chiara
Abstract : Objectives: Evaluation is crucial for integration of e-Health/m-Health into healthcare systems and health technology assessment (HTA) could offer sound methodological basis for these evaluations. Aim of this study was to look for HTA reports on e-Health/m-Health technologies and to analyze their transparency, consistency and thoroughness, with the goal to detect areas that need improvement. Methods: PubMed, ISI-WOS, and University of York – Centre for Reviews and Dissemination–electronic databases were searched to identify reports on e-Health/m-Health technologies, published up until April 1, 2016. The International Network of Agencies for Health Technology Assessment (INAHTA) checklist was used to evaluate transparency and consistency of included reports. Thoroughness was assessed by checking the presence of domains suggested by the European network for Health Technology Assessment (EUnetHTA) HTA Core Model. Results: Twenty-eight reports published between 1999 and 2015 were included. Most were delivered by non-European countries (71.4 percent) and only 35.7 percent were classified as full reports. All the HTA reports defined the scope of research whereas more than 80 percent provided author details, summary, discussed findings, and conclusion. On the contrary, policy and research questions were clearly defined in around 30 percent and 50 percent of reports. With respect to the EUnetHTA Core Model, around 70 percent of reports dealt with effectiveness and economic evaluation, more than 50 percent described health problem and approximately 40 percent organizational and social aspects. Conclusions: E-Health/m-Health technologies are increasingly present in the field of HTA. Yet, our review identified several missing elements. Most of the reports failed to respond to relevant assessment components, especially ethical, social and organizational implications.